Livestock in and around the city - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
There are several organisations with specific support programmes for urban livestock operators, many of them in the livestock rich Sahel. In Burkina Faso, the Centre d étude, de formation et de réalisations agropastorales (Centre for...